Sustainability in sustainability certifications in Thai hotel industry - Sriraksa, Antika; Chaiyakot, Prachyakorn; Luengchavanon, Montri (Edelweiss Applied Science and Technology, 2024)
Thailand is actively working to position itself as a sustainable tourism destination, with sustainability embedded within the nation’s tourism industry framework. Assessment and certification play pivotal roles, serving as essential tools that validate the implementation of sustainable management practices within the accommodation sector. This article explores the concept of sustainable tourism through the lens of widely adopted certifications in Thailand’s hotel industry. A content analysis was conducted to compare certifications based on the Global Sustainable Tourism Council (GSTC) criteria. Furthermore, the study evaluated the efficacy of certifications in promoting the practical integration of sustainable tourism. To deepen the analysis, a thematic review examined the extent to which these certifications integrate principles of Environmental Management Systems (EMSs). The findings highlight a tendency of certification organizations to prioritize environmental aspects over economic and social dimensions. This suggests a need for better alignment in facilitating the holistic integration of sustainable tourism principles into certification practices.